Pengaruh Penambahan Angkak Terhadap Karakteristik Sosis Ikan Lele (clarias gariepinus) Selama Penyimpanan - Elfryani Purba, Zenny; Ayu Ekawati, I Gusti; Mayun Permana, I Dewa Gde (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 2 (2022): Jurnal ITEPA, 2022)
The objective of this study was to know the effect of angkak concentration and storage time on the characteristics of catfish sausage. This research used a Completely Randomized Design with two factors namely the concentration of the angkak (0 %, 1% and 2%) and the length of storage time (0, 7, 14, and 21 days). All of the treatments were repeated two times to obtain 24 units of experiments. The data obtained were analyzed by analysis of variance (ANOVA) and if the treatment had a significant effect, then it was followed by The Duncan Multiple Range Test. The results showed that the concentration of 2% with long storage 7 produce catfish sausage that is still feasible with the criteria: antioxidant capacity 252,80 mg GAEAC/ kg; brightness (L *) 31,03; redness (a *) 20,72; yellowish (b*) 18,81; moisture content 58,95; number of TBA 0,40 mg malonaldehyde / kg; the color slightly liked; flavor, textur, taste and overall acceptance neutral and color red and texture slightly chewy.